The concept of snaching (Al-Salb) and its authenticity in Arabic - Gzaar al-Nasiry, Ghanim Hani; al-Zubaidi , Sabah ‘Etiewi Aboud (International Journal of Psychosocial Rehabilitation, 2020)
The snatching (al-Salb) was mentioned frequently among the Arab linguists scholars in their manifestations, that its meaning by their concern is coercion and removal by hatred obligation, as Ibn Jenni (392 AH) held in its characteristics a door or a chapter for the snatching in which he explained that the snatching is the negation of the positive connotation of the verb or the guarantor noun of its meaning by increasing the structure of the word, as he gave it many examples, including the verb (A’jam) that indicates the presence and clarity, while we find its lexical material indicating to the vagueness, this indication was stolen by increasing the hamza on it, that when the snatching means the coercion and removing events _ as the events manifested by verbs or what like them _ the linguists have limited the indications of the snatching in them, However, we find other means of snatching that are not verbal, that they function as snatching from what it came with. Neither the grammarians nor the morphologists had mentioned them in their records or books, so this research which is entitled (The concept of snatching (al-Salb) and its authenticity in Arabic) came as an attempt to present the concept of the snatching of meaning and its implications